2020
DOI: 10.31557/apjcp.2020.21.2.301
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism in TNF-α-308 G/A and TNF-β +252 A/G, as Prognostic Biomarker in Breast Cancer Patients among Indian Population

Abstract: Background: Cytokines are the key regulator molecules that modulate immune response. Tumor necrosis factor (TNF-α-308 G/A and TNF-β +252 A/G) are inflammatory cytokine that control the progression of several types of cancer. They play a vital role in both tumor progression and destruction based on their concentrations. The role of TNF-α-308 G/A and TNF-β +252 A/G gene polymorphism in the etiology of breast cancer (BC) is not clearly understood. Therefore, present study investigates the association of TNF-α-308… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Results of the study of Ahmad et al. ( 37 ) among an Indian population, suggest that TNF-α-308G/A polymorphism showed significant association with breast cancer patients ( 37 ). Our results show that the mutant TNF-α variant of 308 G/A was significantly associated with increased risk of cachexia in both the pancreatic and NSCL cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the study of Ahmad et al. ( 37 ) among an Indian population, suggest that TNF-α-308G/A polymorphism showed significant association with breast cancer patients ( 37 ). Our results show that the mutant TNF-α variant of 308 G/A was significantly associated with increased risk of cachexia in both the pancreatic and NSCL cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Skoog et al proposed that TNF-α − 863 C/A polymorphism affects the binding of nuclear protein(s) to the promoter region of the TNF-α gene, with accompanying changes in TNF-α expression, thus leading to variation in TNF-α levels [ 55 ]. The role of ethnicity may also play a role as well, carriers of the rare ‘A’ allele have a significantly lower TNF-α levels in Swedish and Indian population [ 55 , 56 ], while they have a significantly higher levels in Japanese population [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of all other TNF-α SNPs, − 308 G/A is the most studied SNP. This SNP is also correlated with the risk of other cancer, such as breast cancer and gastric cancer [ 56 , 58 ]. This SNP seems to be variable within ethnicities, as in meta-analysis study conducted by Wei et al, SNP − 308 AA was associated with an increased risk of HCC in Asian ethnicities, but not for Caucasian [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently were reported mutations of immune players as biomarkers, analyzed for specific human populations, Ahmad et al 104 reported the TNF-a308 G/A change and its significant association with breast cancer patients from north India and over the major histocompatibility complex class I-related chain A (MICA). Ouni et al 105 reported the MICA-129 Met/Val change as an inherited genetic biomarker contributing to an increased breast cancer risk in Tunisian women.…”
Section: Strategies For the Search Of New Biomarkersmentioning
confidence: 99%